Association Between Pain and Functional Independence in Older Adults During and After Admission to Rehabilitation After an Acute Illness or Injury. Issue 11 (4th November 2015) - Rodriguez, Juan C.; Dzierzewski, Joseph M.; Fung, Constance H.; Jouldjian, Stella; Josephson, Karen R.; Mitchell, Michael N.; Song, Yeonsu; Martin, Jennifer L.; Alessi, Cathy A.
Abstract : Objectives: To investigate the association between pain and functional independence in older adults during and after admission to rehabilitation after an acute illness or injury. Design: Prospective, observational cohort study. Setting: One community and one Veterans Affairs rehabilitation center. Participants: Individuals aged 65 and older admitted for rehabilitation after an acute illness or injury (postacute rehabilitation) (N = 245; mean age 80.6, 72% male)). Measurements: Pain was assessed using the Geriatric Pain Measure (GPM, score 0–100). Functional independence was measured using the motor component of the Functional Independence Measure (mFIM, score 13–91). Both scores were obtained at admission; discharge; and 3‐, 6‐, and 9‐month follow‐up. In bivariate analyses, discharge GPM and persistent pain (lasting >3 months) were evaluated as predictors of mFIM score at 9 months. Applying a multilevel modeling (MLM) approach, individual deviations in GPM scores were used to predict variations in mFIM. Results: At admission, 210 participants (87.9%) reported pain (16.3% mild (GPM<30); 49.3% moderate (GPM: 30–69); 22.1% severe (GPM>70)); 21.3% reported persistent pain after discharge. The bivariate analyses did not find statistically significant associations between discharge GPM or persistent pain and mFIM score at 9 months, but in the MLM analysis, deviations in GPM were significant predictors of deviations in mFIM score, suggesting that, when individuals experienced above‐average levels of pain (GPM > their personal mean GPM), they also experienced worse functional independence (mFIM < their personal mean mFIM). Conclusion: Twenty‐one percent of older adults undergoing postacute rehabilitation reported persistent pain after discharge from rehabilitation. The bivariate analysis did not find association between pain and functional independence, but MLM analysis showed that, when participants experienced more pain than their average, they had less functional independence.